Pengaruh Model Pembelajaran Flipped Classroom dan Gaya Kognitif Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Deni Pratidiana; Heni Pujiastuti; Cecep AHF Santosa (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This study examines the effect of the flipped classroom learning model and cognitive style on students' mathematical problem solving abilities. The type of quasi-experimental research with the sample technique is cluster random sampling. The population is all students of class XI SMAN 11 Pandeglang, with a sample of 2 classes for 1 experimental class with flipped classroom and 1 control class with conventional. The stages of the research were giving the GEFT test to classify based on cognitive style. Then pretest, treatment and finally given posttest. The test instrument is in the form of 4 essay questions that have been tested using the CVR method. The data analysis technique used was to determine descriptive statistics, pretest and posttest scores, normality and homogeneity tests of N-gain data and Two Way Anova analysis. The results of statistical tests show that 1) there are differences in the improvement of mathematical problem solving abilities of students who use the flipped classroom model with students who use conventional models, 2) there are differences in the improvement of mathematical problem solving abilities between students who have a field independent cognitive style and students who have a cognitive style. field dependent on flipped classroom learning, 3) there is an interaction between the learning model and cognitive style on increasing students' mathematical problem solving abilities.